Über das Vorkommen von Frost auf Java/Indonesien, insbesondere in den Pengalengan Highlands - Domrös, Manfred (ERDKUNDE, 1976)
Carl Troll was the first to draw special attention to the ecologically most important phenomenon of noctural radiation or ground frost in frost holes of tropical high mountains, mainly those of the Andes and the Ethiopian High lands. The author attemps to study this phenomenon in the volcanic mountains of Java for which the incidence of frost has not yet been investigated systematically. Through the analysis of temperature records of Mount Pangerango (3023 m) and of various tea estates in the Pengalengan Highlands (1500-2300 m), Western Java, as well as the phenological study frost of damage to tea bushes, it became clear that light nocturnal ground frosts may occur during the Southern winter from July up to September. Frosts occur at an elevation above 1500 m in drepessions only, whereas slopes -even at much higher elevation-are frost free. Frosts in the mountains of Java represent a typical local climatological phenomenon, favoured by the volcanic small-scale topography. Besides, frosts were recorded during the dry season of the winter only, and the validity of the principal rule is therefore confirmed that a dry period means a greater risk of frost, a wet period a lesser risk. Anthropogenic measurements of frost protection, for example drains or artificial heating, have been too expensive and scarcely successful as experiences of tea estates have shown.